Microfacies Analysis and Diagenesis Processes of Mauddud Formation in selected wells from Ratawi oil field, Southern Iraq - Hussain, Salah; Lateef Hameed, Mustafa (ASJ - Academic Science Journal, 2024)
Mauddud Formation was studied in Ratawi oil field, Southern Iraq. The lithology of the formation is limestone in all studied wells (Rt-2, Rt-4, Rt-17 and Rt-19). lower contact of Mauddud Formation with Nahr Umr Formation is gradational, but the upper contact is unconformable with Ahmadi Formation.In this work, 114 thin sections were examined and shows four microfacies (wackestone, packstone, grainstone and argillaceous mudstone), which deposited in the Inner-Mid to Outer ramp environment. The most significant diagenesis processes were micritization, dissolution, cementation, compaction, and dolomitization, which had an impact on the texture and porosity of the Mauddud Formation.